Influence of Peer-Based Needle Exchange Programs on Mental Health Status in People Who Inject Drugs: A Nationwide New Zealand Study - Hay, Bianca; Henderson, Charles; Maltby, John; Canales, Juan J. (Frontiers in Psychiatry, 2017)
Alleviating the personal and social burden associated with substance use disorders requires the implementation of a comprehensive strategy, including access to needle exchange programmes (NEP), psychiatric treatment, outreach, education and community interventions. In light of the substantial research underscoring the potential benefits of peer support in psychiatric interventions, we conducted a national survey to examine key domains of mental health status in people who inject drugs (PWID) in New Zealand. PWID were recruited from 24 pharmacies and 16 dedicated peer-based needle exchanges (PBNEs) across the country. We focused on two mental health outcomes: (1) affective dysregulation, across the three emotional domains of the DASS scale, for its role in the maintenance of continued drug use, and (2) positive cognition and effective health- and drug-related information exchange with the provider, using the Satisfaction with Life Scale (SWLS) and an ad hoc questionnaire, respectively, for their association with improved mental health outcomes. Remarkably, multi-step regression analysis revealed that, irrespective of sex, age, ethnicity, main drug used, length of drug use, and frequency of visits to the NEP, the exclusive or preferential use of PBNEs predicted lower depression and anxiety scores, greater satisfaction with life, and increased health-related information exchange. These findings demonstrate for the first time an association between access to peer support at PBNEs and positive indices of mental health, lending strong support to the effective integration of such peer-delivered NEP schemes into the network of mental health services for PWID worldwide.